Model Akta Notaris Yang Melindungi Para Pihak Dalam Perjanjian Peralihan Hak Atas Varietas Tanaman (PVT) - Annalisa Yahanan; Debbie Aprodette; Elmandiantini (Recital Review, 2020)
The Notary deed model that protects parties in the Agreement on the Transfer of Rights to Plant Varieties. This study is a normative legal research with the legal type and materials obtained from secondary data, collected through library studies, with deductive deduction techniques. The results of this study are, currently the Notary deed model in the Transfer of the Rights to Plant Varieties does not yet exist or has not been made standardly by the Notary because the PVP rights transfer deed is still made under the hand, whereas, UUPVT regulates explicitly that the PVP rights transfer agreement must use a Notary Deed. The role of Notary in making the deed of agreement for the transfer of rights to cultivating plant varieties is beside to making the deed of agreement on the cultivation rights of plant varieties which is then stated in the Notary deed as stipulated in the law, also providing legal counseling to the parties regarding the PVP rights transfer agreement. The Notary deed model in the transfer of rights to plant varieties that can provide protection for the parties (breeders and recipients of plant breeders) is to include the contents of the agreement on the transfer of PVP rights into clauses that do not harm the parties who do not violate the principles in the law agreement. Notary deeds are required in the transfer of rights to PVP because it has a high value where in creating a variety of plants it requires relatively expensive costs and a relatively long time, when compared to other intellectual property.